Do Lower Tariff Rates Promote Global Value Chain Participation? - Yanikkaya, Halit; Tat, Pinar; Altun, Abdullah (Cambridge Univ Press, 2024)
The trade of intermediates now accounts for a growing share of global trade. In this highly fragmented global production system, any change in tariff rates can generate a higher impact than that of initial direct tariffs. To assess the impact of tariffs on global value chain participation, this study uses value-added trade statistics and cumulative tariff rates for 12 sectors from 168 countries for the years 1990-2015. The visual inspection suggests that initial tariffs result in higher tariff rates (almost 14%) due to a knock-on impact along with supply chains. The main empirical finding is that both faced and imposed tariff rates have significant negative impacts on sectoral global value chain participation. The effect is also persistent in the analysis if we employ cumulative tariff rates. Apart from these policy determinants, sector- and country-level endowments, such as higher relative length, capital intensity, foreign direct investment stock, and human capital appear to be the major drivers for higher total, forward, and backward global value chains participation. Even if our main results are robust, there are also some distinctions in the effects of tariff rates depending on the country- and sector-level heterogeneities. In a policy-related debate, given the cascading impacts of these liberalization initiatives, autonomous, regional, and global liberalization efforts are critical for all sectors to reap the benefits from the global production system.
Keywords: Input tariff; cumulative tariff; global value chains